Arrhythmic activity in the left frontal eye field facilitates conscious visual perception in humans. (October 2015) - Chanes, Lorena; Quentin, Romain; Vernet, Marine; Valero-Cabré, Antoni
Abstract: The frontal eye field (FEF) is a brain region involved in several processes relevant for visual performance, including visuo-spatial attention, conscious access and decision-making. Prior research has causally demonstrated that high-beta FEF activity in the right hemisphere enhances conscious visual perception, an outcome that is in agreement with evidence of neural synchronization along a right dorsal fronto-parietal network during attentional orienting and a right-hemisphere dominance for visuospatial processing. Nonetheless, frontal regions in the left hemisphere have also been shown to modulate perceptual performance. To causally explore the neural basis of these modulations, we delivered high-beta frequency-specific bursts of transcranial magnetic stimulation (TMS) to the left FEF and report that, in this region, these patterns failed to modulate conscious perception. In contrast, non-frequency-specific TMS patterns yielded visual performance improvements similar to those formerly causally associated to the induction of high-beta activity on its right-hemisphere homotopic area. This noise-induced facilitation of conscious vision suggests a relevant role of the left frontal cortex in visual perception. Furthermore, taken together with prior causal right-FEF evidence, our study indicates that frontal regions of each hemisphere employ different coding strategies to modulate conscious perception.